Enhancing the Thermoelectric Properties of the Electroplated Bi2Te3 Films by Tuning the Pulse Off-to-on Ratio. (1st October 2015) - Zhou, Aijun; Fu, Qiang; Zhang, Wenhua; Yang, Bin; Li, Jingze; Ziolkowski, Pawel; Mueller, Eckhard; Xu, Dongyan
Abstract: The electroplating method has been widely used to synthesize Bi2 Te3 thin films due to many advantages including low cost, non-vacuum operation, and compatibility with microfabrication processes. However, the structure-property correlation of the electroplated Bi2 Te3 thin films has not been well studied yet due to a lack of systematic properties characterization. In this work, we systematically studied the dependence of the composition, microstructure, and thermoelectric properties on the deposition parameters for the Bi2 Te3 thin films prepared by the pulsed electroplating method. It is shown that a deposition pulse potential of 0 mV vs . Ag/AgCl (saturated KCl) and a large pulse off-to-on ratio are advantageous to improve the stoichiometry and morphology of the deposited films. We demonstrated that the thermoelectric figure of merit of the electroplated Bi2 Te3 films can be enhanced by increasing the pulse off-to-on ratio, which is mainly due to the reduced thermal conductivity and the increased Seebeck coefficient. At room temperature, a maximum thermoelectric figure of merit of 0.16 is obtained at a pulse off-to-on ratio of 50, which is among the highest values for the electroplated Bi2 Te3 films.